2022
DOI: 10.3390/d14030210
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Genotyping of Two Bulgarian Sheep Breeds

Abstract: The aim of this study was to compare the genetic structure and genetic diversity of two Bulgarian sheep breeds. A total of 41 individuals from a modern Bulgarian sheep population (Rhodopean Tsigai, RT) and 46 representatives of a local Bulgarian sheep population (Middle Rhodopean Sheep, MRS) were investigated based on 12 STR (short tandem repeat, also known as microsatellite) markers. In total, 121 alleles were found in the two populations using 12 microsatellite loci. The mean number of alleles, the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Such value show the diversity among local sheep breeds which used in this study. The Shannon index value in the present study was lower in comparison to (Odjakova, et al, 2022) in two Bulgarian sheep breeds (I = 1.79), also (Sharma, et al, 2020) reported higher index in Indian native sheep breeds (1.56). (Alnajm, 2020) observed higher I value in some Iraqi sheep breeds by ssr marker (I=0.965).…”
Section: Resultscontrasting
confidence: 60%
“…Such value show the diversity among local sheep breeds which used in this study. The Shannon index value in the present study was lower in comparison to (Odjakova, et al, 2022) in two Bulgarian sheep breeds (I = 1.79), also (Sharma, et al, 2020) reported higher index in Indian native sheep breeds (1.56). (Alnajm, 2020) observed higher I value in some Iraqi sheep breeds by ssr marker (I=0.965).…”
Section: Resultscontrasting
confidence: 60%
“…Fis was positive in all breeds with the exception of MK, which indicates an excess of homozygotes and may also be a reason for the observed deviations from HWE in these breeds. However, the comparative analysis with previous studies [2,4,35] showed that the level of inbreeding has not increased in the autochthonous Bulgarian sheep breeds during the last 10 years. This is probably due to the increased size of the populations and the inclusion of new flocks under selection control, which allows for the more effective implementation of inbreeding avoidance schemes.…”
Section: Discussionmentioning
confidence: 79%
“…There have not been systematic molecular studies covering a large number of sheep breeds in Bulgaria up until now, only small-scale molecular investigations including a few autochthonous sheep breeds and/or a few microsatellite markers [2][3][4][5][6]. Among the DNA marker systems used today, microsatellites (simple sequence repeats (SSR)) and SNP (single nucleotide polymorphism) have proven to be the most applicable markers for paternity testing; gene diversity assessment; analysis of the genetic structure and inbreeding; QTL mapping; and in population and evolutionary genetics in a range of animal species, including sheep [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of studies on the genetic diversity among native Bulgarian sheep have been performed only on autosomal short tandem repeat variations (STR, microsatellites) [39][40][41][42][43][44]. In this research, carried out in 2023, we evaluated for the first time the genetic diversity of eight native Bulgarian sheep breeds which are threatened with extinction, based on the sequence polymorphism of the mitochondrial control region (D-loop region).…”
Section: Introductionmentioning
confidence: 99%